MEMBANGUN KEPEMIMPINAN MUDA OSIS SMK YAPIA PARUNG MENUJU ERA 5.0 MELALUI KEGIATAN SOSIAL BERBASIS DIGITAL - Munthe, Winda Ludovika; Faleri, Cyntia; Indarni, Yustina Dwi; Nisa, Halimah Chairun; Yasa, I Made Rahayu Kardika; Pujilestari, Yulita (MAJU : Indonesian Journal of Community Empowerment, 2025)
In facing the challenges of the 5.0 era, where technology is at the center of various human activities, adaptive, innovative, and technology-based young leadership is an urgent need. This study aims to develop the leadership of OSIS SMK Yapia Parung students through the implementation of digital-based social activities that are in line with the values ​​of the 5.0 era. Using a participatory approach, this study designed a program that involved digital technology in the planning, implementation, and evaluation of social activities. The results showed that students experienced significant improvements in digital leadership skills, including communication, organizational, and program management skills through digital platforms. Student creativity also increased with the use of social media and collaboration applications to organize activities such as online donation campaigns and educational webinars. In addition, the social impact of this activity was seen in the form of increased public awareness of local issues and students' ability to reach a wider audience. In conclusion, this digital-based social activity program is effective in building the character of young leaders who are relevant to future needs, while providing real social impacts for the community. This study recommends the development of similar programs on a larger scale, increasing digital training for students, and collaborating with external partners to expand the impact of activities.